THE UTILIZATION OF MICROSOFT SWAY IN PANCASILA EDUCATION LEARNING - Wicaksono, Setyo Pambudi; Wibawa, Sutrisna (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
In the current educational landscape, Pancasila Education must integrate the principles of 21st-century learning, which emphasize the importance of technology utilization in education. The integration of media enhances the learning process, making it more accessible, engaging, effective, and efficient. This study seeks to explore how Microsoft Sway media is utilized in Pancasila Education classes at Kejambon 2 Public Elementary School. Utilizing a qualitative descriptive research method, the study investigates the impact and effectiveness of Microsoft Sway in enhancing Pancasila Education learning experiences. The research findings reveal that Microsoft Sway aligns well with the principles of 21st-century learning. It fosters increased student engagement and enthusiasm, shifting the focus of learning activities towards student-centered approaches. This integration not only modernizes the teaching-learning process but also nurtures critical thinking and active participation among students, thus enriching their understanding and appreciation of Pancasila values and principles.Keywords: Microsoft Sway, Pancasila Education, 21st-century learning.